Killing Hercules - Rowland, Richard, 1955-, author.
1 online resource
Keywords: "Each chapter of this book offers a detailed account of the ways in which different cultures - the ancient Greek democracy, imperial Rome, early Christianity, the emergent vernacular cultures of late medieval and early modern Europe, the Enlightenment - have re-evaluated the story of Hercules and his wife and killer Deianira, in the light of their own attempts to come to terms with the phenomena of military and domestic violence."--